Screening and profiling of blood pressure and glucose levels for early detection of hypertension and diabetes mellitus in Olak Kemang RT 02 community - Maharni, Indri; Elisma; Maimum; Perawati, Santi; Kamilah, Nurul; Pondawinata, Marizki; Neldi, Vina; Astuti, Novia Tri (Proceedings Academic Universitas Jambi, 2025)
Background: Hypertension and diabetes mellitus are highly prevalent non-communicable diseases and major causes of morbidity and mortality. Their asymptomatic nature in early stages often delays diagnosis, increasing the risk of serious complications. Early detection through community-based screening is therefore essential. Objective: This program aimed to assess blood pressure and glucose profiles of RT 02 Olak Kemang residents in Jambi City and to promote awareness of regular health monitoring. Methods: The program screened 25 residents aged ≥30 years using a digital sphygmomanometer for blood pressure and a glucometer for random blood glucose. Participants also received education on healthy lifestyles, including diet, physical activity, and routine check-ups. Results: Results demonstrated that a number of participants presented with above-normal blood pressure and glucose levels, highlighting potential susceptibility to hypertension and diabetes mellitus. These outcomes emphasize the presence of unrecognized health risks which could lead to severe complications without proper management. Conclusion: This program generated initial health profile data of Olak Kemang RT 02 residents while improving community awareness on early detection and prevention of non-communicable diseases. Integrating community-based screening with health education is crucial to encourage healthy behaviors and lessen disease burden.